2020
DOI: 10.1155/2020/4705149
|View full text |Cite
|
Sign up to set email alerts
|

Peptidomics Analysis Discloses That Novel Bioactive Peptides Participate in Necrotizing Enterocolitis in a Rat Model

Abstract: Necrotizing enterocolitis (NEC) is a common devastating gastrointestinal disease in premature infants, the molecular mechanisms of which have not been fully elucidated. Recently, endogenous peptides have garnered much attention owing to their role in diagnosis and treatment. However, changes in the peptide expression of NEC intestinal tissues remain poorly understood. In the present study, a comparative peptidomics profiling analysis was performed between NEC and control intestinal tissues via liquid chromatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The activity of antimicrobial peptides in inhibiting the bacterial lesions in the digestive tract has been reported, and the blocking effect on bacterial nucleic acid formation and the promotion of bacterial cell membrane perforation hole formation are the potential tactics . Accumulating evidence also indicates that epithelial apoptosis represents an important component in the gastrointestinal damage induced by the pathogenesis of bacterial infection-mediated inflammation, and the effective inflammation control strategies have the potential for ameliorating of necrotizing enterocolitis. , The effect of dietary supplementation of antioxidant peptides on the phenotype of necrotizing enterocolitis in mouse model suggested that antioxidant peptides could ameliorate inflammation in necrotizing enterocolitis through attenuating ROS-NF-κB axis . Results of mouse models that were given various dietary regimen also illustrated that active peptides with anti-inflammatory effects were also evidenced to have a beneficial therapeutic effect in necrotizing enterocolitis by reducing inflammation and tight junction disruption .…”
Section: Resultsmentioning
confidence: 99%
“…The activity of antimicrobial peptides in inhibiting the bacterial lesions in the digestive tract has been reported, and the blocking effect on bacterial nucleic acid formation and the promotion of bacterial cell membrane perforation hole formation are the potential tactics . Accumulating evidence also indicates that epithelial apoptosis represents an important component in the gastrointestinal damage induced by the pathogenesis of bacterial infection-mediated inflammation, and the effective inflammation control strategies have the potential for ameliorating of necrotizing enterocolitis. , The effect of dietary supplementation of antioxidant peptides on the phenotype of necrotizing enterocolitis in mouse model suggested that antioxidant peptides could ameliorate inflammation in necrotizing enterocolitis through attenuating ROS-NF-κB axis . Results of mouse models that were given various dietary regimen also illustrated that active peptides with anti-inflammatory effects were also evidenced to have a beneficial therapeutic effect in necrotizing enterocolitis by reducing inflammation and tight junction disruption .…”
Section: Resultsmentioning
confidence: 99%